Challenges of nursing teaching-learning to care for human dying - professors' perceptions - Emanuelle Caires Dias Araújo Nunes; Andressa de Andrade Santos (Universidade Federal do Rio de Janeiro, 2017)
Abstract The objective of this study was to investigate professors' perceptions about their experiences in the teaching-learning process of nursing care in relation to dying. This is a descriptive-exploratory, qualitative research, delimited by data saturation, was carried out with 11 nursing professors from three higher education institutions. Data collection involved the drawing-text theme technique and a semi-structured interview. Analysis used the technique of collective subject discourse. The results identified three categories: How I would like to take care in the context of finitude - my challenge; Challenging fragilities in the teaching of nurses in the context of care concerned with death and dying; Strategies to compensate or promote more substantial nurse training related to care in finitude. We conclude that the graduation of the nurses studied did not satisfactorily develop the necessary skills and abilities to deal with human death and dying. This study infers the need of permanent education to support transformations in this area.